Secure Multi-objective Hybrid Routing Protocol For Wireless Sensor Network - Kaushik, Ruchi; Singh, Vijander; Kumari, Rajani (Recent Patents on Engineering, 2021)
Background: Wireless sensor networks play a significant role in network technologies. It is difficult to determine an optimal route that satisfies the requirements of wireless sensor networks. Energy- aware and trust-aware routing protocols play a critical role in the security of wireless sensor networks. SRPMA routing protocols have limited parameters and functions. The ant colony algorithm is specifically designed to find the roots in which convergence is limited. Objective: This paper proposed an improved multi-objective trust-energy aware hybrid routing protocol using a hybrid grey wolf genetic algorithm (I-MTERP-GWOGA) to achieve quality service by optimizing network security and reducing energy consumption in wireless sensor networks. Methods: Energy-aware function calculated by the radio energy dissipation model ensures if the nodes involved in the route are capable of transmitting the data packets successfully or not. The load function directly impacts the delay of the transmission of data packets. Results: I-MTERP-GWOGA algorithm shows better simulation results than secure routing protocol based on multi-objective ant-colony (SRPMA) and improved ant colony optimization based security routing protocol (IASR) algorithms using MATLAB 2019a. Conclusion: The proposed algorithm improves performance against malicious nodes using five network performance criteria; packet delivery ratio, packet loss rate, average energy consumption, and end to end delay.
Keywords: grey-wolf optimization